The Role of Diverse Liver Cells in Liver Transplantation Tolerance - Jiang, Yanzhi; Que, Weitao; Zhu, Ping; Li, Xiao-Kang (Frontiers in Immunology, 2020)
Liver transplantation is the ideal treatment approach for a variety of end-stage liver diseases. However, life-long, systemic immunosuppressive treatment after transplantation is required to prevent rejection and graft loss, which is associated with severe side effects, although liver allograft is considered more tolerogenic. Therefore, understanding the mechanism underlying the unique immunologically privileged liver organ is valuable for transplantation management and autoimmune disease treatment. The unique hepatic acinus anatomy and a complex cellular network constitute the immunosuppressive hepatic microenvironment, which are responsible for the tolerogenic properties of the liver. The hepatic microenvironment contains a variety of hepatic-resident immobile non-professional antigen-presenting cells, including hepatocytes, liver sinusoidal endothelial cells, Kupffer cells and hepatic stellate cells, that are insufficient to optimally prime T cells locally and lead to the removal of alloreactive T cells due to the low expression of major histocompatibility complex (MHC) molecules, costimulatory molecules and proinflammatory cytokines but a rather high expression of coinhibitory molecules and anti-inflammatory cytokines. Hepatic dendritic cells (DCs) are generally immature and less immunogenic than splenic DCs and are also ineffective in priming naïve allogeneic T cells via the direct recognition pathway in recipient secondary lymphoid organs. Although natural killer cells and natural killer T cells are reportedly associated with liver tolerance, their roles in liver transplantation are multifaceted and need to be further clarified. Under these circumstances, T cells are prone to clonal deletion, clonal anergy and exhaustion, eventually leading to tolerance. Other proposed liver tolerance mechanisms, such as soluble donor MHC class I molecules, passenger leukocytes theory and a high-load antigen effect, have also been addressed. We herein comprehensively review the current evidence implicating the tolerogenic properties of diverse liver cells in liver transplantation tolerance.